2016
DOI: 10.1161/circulationaha.116.021516
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Type, and Volume of Leisure-Time Physical Activity and Risk of Coronary Heart Disease in Young Women

Abstract: Background The inverse association between physical activity and coronary heart disease (CHD) risk has primarily been shown in studies of middle-aged and older adults. Evidence for the benefits of frequency, type, and volume of leisure-time physical activity in young women is limited. Methods We conducted a prospective analysis among 97,230 women aged 27-44 years at baseline in 1991. Leisure-time physical activity was assessed biennially by questionnaire. Cox proportional hazards models were used to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 32 publications
(33 reference statements)
0
34
0
1
Order By: Relevance
“…Excess bodyweight on the contrary has shown to increase the risk for CHD and in particular MI by 20-60% in overweight and obese individuals respectively, compared with those of normal weight [8][9][10] . Most studies examining the joint effects of physical activity and body mass index (BMI) on CVD and CHD have reported that physical activity attenuated but did not fully eliminate the increased CVD risk associated with overweight and obesity [11][12][13][14][15][16] . However, one recent study showed that overweight and obese active individuals do not have an elevated CVD risk when compared to normal weight, active individuals 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess bodyweight on the contrary has shown to increase the risk for CHD and in particular MI by 20-60% in overweight and obese individuals respectively, compared with those of normal weight [8][9][10] . Most studies examining the joint effects of physical activity and body mass index (BMI) on CVD and CHD have reported that physical activity attenuated but did not fully eliminate the increased CVD risk associated with overweight and obesity [11][12][13][14][15][16] . However, one recent study showed that overweight and obese active individuals do not have an elevated CVD risk when compared to normal weight, active individuals 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, one recent study showed that overweight and obese active individuals do not have an elevated CVD risk when compared to normal weight, active individuals 17 . Most previous studies were conducted in single sex only [11][12][13]15 , and examined either the associations of physical activity and obesity with CVD 12,16,17 or CHD 11,[13][14][15] . The exposure of interest in earlier research was LTPA [11][12][13]15,17 or a combination of occupational and leisure-time physical activity 14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The inverse association between physical activity and cardiovascular disease (CVD) is well established, with both moderate‐ to vigorous‐intensity exercise as well as brisk walking having cardiovascular benefits 1, 2, 3, 4. Furthermore, this inverse association has been shown in various high‐risk subgroups, including older adults, current smokers, and adults with diabetes mellitus (DM), hypercholesterolemia, or hypertension 2, 3, 5, 6, 7, 8, 9, 10.…”
mentioning
confidence: 99%
“…While there are opportunities to explore strategies to reduce television and video game use, overall, the amount of daughters' and mothers' self-reported PA behaviors suggest that both are amenable to PA. In light of current literature that suggests that even leisurely total volume (frequency, type and duration) of PA is related to lower risk of coronary heart disease (Chomistek, Henschel, Eliassen, Mukamal, & Rimm, 2016), this finding of this sample's PA is promising and can serve as a foundation to build upon their current positive PA behaviors.…”
Section: Discussionmentioning
confidence: 85%